Spatially Varying Stress State in the Central U.S. From Bayesian Inversion of Focal Mechanism and In Situ Maximum Horizontal Stress Orientation Data. Issue 5 (8th May 2018) - Carlson, Grace; Johnson, Kaj; Chuang, Ray; Rupp, John
Abstract: The crustal stress state in the Midcontinent of the United States has been a focus of research for many years due to anomalously high rates of seismicity in the region. This interest is recently renewed because of ongoing wastewater injection and CO2 sequestration in the Illinois Basin and its potential to induce seismicity. When fluid is injected, pore pressure increases, decreasing effective normal stress and increasing the potential for faults optimally oriented with respect to the direction of maximum compressive stress to slip. In order to better manage this risk, we present a study on the spatial distribution of principal stress orientations in the Illinois Basin and surrounding region using focal mechanism solutions and in situ measured maximum horizontal stress orientation indicators from borehole breakout, core fracture, overcoring, hydraulic fracture, and strain gauge measurements. To invert these data for the deviatoric stress tensor, we extend the damped‐least stress inversion of Hardebeck and Michael (2006, https://doi:10.1029/2005JB004144 ) with the mixed linear/nonlinear Bayesian inversion scheme of Fukuda and Johnson (2010, https://doi:10.1111/j.1365‐246X.2010.04564.x ). The stress inversion provides an objective means to estimate nonlinear parameters including the spatial smoothing parameter, unknown data uncertainties, and selection of focal mechanism nodal planes. Results indicate a systematic rotation of the maximum horizontal stress orientation ( S Hmax ) across a 1, 000‐km width of the Midcontinent. S Hmax rotates from ~N60°E to ~E/W orientation across the southern Illinois Basin. The principal stress orientations are largely consistent with the observed pattern of strike‐slip faulting and reverse faulting near the New Madrid and Wabash Valley Seismic Zones. Key Points: Maximum horizontal stress orientations rotate from a regional trend of ~N60°E to ~E/W near the New Madrid and Wabash Valley Seismic Zones Localized reverse‐faulting stress regime in the New Madrid and Wabash Valley Seismic Zones deviates from regional strike‐slip stress regime We objectively solve for the spatial smoothing parameter, data uncertainties, and selection of the focal mechanism nodal planes